Regionalna lingvistična atlasa: Istriotski lingvistični atlas (ILA), Istroromunski lingvistični atlas (IRLA) - Filipi, Goran (Slavia Centralis, 2020)
Regional Linguistic Atlases: the Istriot Linguistic Atlas (ILA) and the Istroromanian Linguistic Atlas (IRLA)The author discusses his regional atlases: the first is Istrian (ILA; published in 1998) and the second is Istro-Romanian (IrLA; 2002). In the first part of the article, he presented a questionnaire of both atlases and basic data on Istrian and Istro-Romanian. The following are selected excerpts from the pens of established linguists who have written about the ILA and IrLA. All abstracts are in the original language, without translation.
Keywords: regional linguistic atlas; Istriot Linguistic Atlas (ILA); Istroruomanian Linguistic Atlas (IRLA); Istrian; Istroromanian